First Total Syntheses of (±)-Callyspongidic Acids and 2-epi-(±)-Callyspongidic Acids - Das, Sayani; Bala, Anju; Sharma, Kapil; Gholap, Shivajirao L. (Synthesis, 2022)
The first total syntheses of (±)-callyspongidic acids and 2-epi-(±)-callyspongidic acids were achieved in high overall yield from epoxy ester derived from commercially available l-(+)-tartaric acid. The key features of these syntheses are the stereoselective opening of epoxide with organocuprates and the chemoselective addition of Grignard reagent to ketone in the presence of ester. The synthetic route reported here is operationally simple, very short and amenable for the synthesis of several analogues of this class.
Keywords: alkyl citrates; callyspongidic acids; natural products; tartaric acid; total synthesis